If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(m + 3) = 2(3m + 1) Reorder the terms: 5(3 + m) = 2(3m + 1) (3 * 5 + m * 5) = 2(3m + 1) (15 + 5m) = 2(3m + 1) Reorder the terms: 15 + 5m = 2(1 + 3m) 15 + 5m = (1 * 2 + 3m * 2) 15 + 5m = (2 + 6m) Solving 15 + 5m = 2 + 6m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-6m' to each side of the equation. 15 + 5m + -6m = 2 + 6m + -6m Combine like terms: 5m + -6m = -1m 15 + -1m = 2 + 6m + -6m Combine like terms: 6m + -6m = 0 15 + -1m = 2 + 0 15 + -1m = 2 Add '-15' to each side of the equation. 15 + -15 + -1m = 2 + -15 Combine like terms: 15 + -15 = 0 0 + -1m = 2 + -15 -1m = 2 + -15 Combine like terms: 2 + -15 = -13 -1m = -13 Divide each side by '-1'. m = 13 Simplifying m = 13
| (94)=136 | | 3x^2-x+7=0 | | -91-9x=-3x+35 | | -112+128x-16x^2=0 | | 4x+11y=3 | | (49)=70 | | -20-3x=28+x | | (70)=49 | | 8x-48=5x+33 | | (55)=110 | | -20x+10y=50 | | -80-5x=112+7x | | -6x-161=7x+47 | | -25=q-.2q^2 | | 25q=.2q^2 | | -1.6=4.8+1.6x | | -3x+14=0 | | x+0.2=0.4x+3.2 | | 8d+4d-5d-8-5d=0 | | -4a+2=-8-14 | | 6(m+3)+m+12=0 | | n-8=-11 | | -2.4=-1.5x-1.7 | | 5x^2-12x^2+7=0 | | 3x+.63-2x-.25=.63 | | 820-71= | | 2.5s-2+3(s-11)=50 | | 25s-2+3(s-11)=50 | | -2(3+4x)=18 | | -49+f=9 | | w^2-10w+15=0 | | 2(56+24r)=-1r |